Novel fluoroquinolones containing 2-arylamino-2-oxoethyl fragment: Design, synthesis, evaluation of antibacterial and antituberculosis activities and molecular modeling studies - TÜRE, ASLI; KÜÇÜKGÜZEL, İLKAY; KULABAŞ, NECLA (WILEY, 2022)
Novel substituted fluoroquinolone derivatives, compounds 6-20 were designed, synthesized, and evaluated for antituberculosis and antibacterial activity. Antibacterial activities of the compounds were determined and compound 14 was found to be the most potent antimicrobial agent owing to minimal inhibitory concentration (MIC) value of <1.16 mu g/mu l for all tested bacteria. Further, compounds were tested in vitro for their antimycobacterial activity against Mycobacterium tuberculosis H37Rv. Most of the compounds showed antimycobacterial effects with 1.56-25.00 mu g/ml MIC values. Compounds 14 and 18 were found to be the most active derivatives due to their MIC at 1.56 mu g/ml. Selected compounds 11, 14, 17, and 18 were tested for M. tuberculosis DNA supercoiling assay and they had IC50 values within a range of 6.35-15 mu M. Mechanism of binding to DNA gyrase enzymes was evaluated using in silico molecular modeling studies and it was shown that compounds 6-20 adopt a similar binding mode as already known for fluoroquinolone drugs.
Keywords: MICROWAVE-ASSISTED SYNTHESIS; MYCOBACTERIUM-TUBERCULOSIS; BIOLOGICAL EVALUATION; ANTIMYCOBACTERIAL EVALUATION; DERIVATIVES; CIPROFLOXACIN; MOXIFLOXACIN; ANTICANCER; GATIFLOXACIN; INHIBITION